Precise Investigation of the Efficacy of Multicomponent Drugs Against Pneumonia Infected With Influenza Virus - Wei, Junying; Sun, Jianhui; Zeng, Jiawei; Ji, Enhui; Xu, Jing; Tang, Chunyu; Huo, Hairu; Zhang, Yi; Li, Hongmei; Yang, Hongjun (Frontiers in Pharmacology, 2021)
Background: Viral pneumonia is one of the most serious respiratory diseases, and multicomponent traditional Chinese medicines have been applied in the management of infected patients. As a representative TCM, HouYanQing (HYQ) oral liquid shows antiviral activity. However, the unclear mechanisms, as well as the ambiguous clinical effects, limit widespread application of this treatment. Therefore, in this study, a proteomics-based approach was utilized to precisely investigate its efficacy. Methods: Based on the efficacy evaluation of HYQ in a mouse model of pneumonia caused by influenza A virus (H1N1) and the subsequent proteomics analysis, specific signatures regulated by HYQ treatment of viral pneumonia were identified. Results: Experimental verifications indicate that HYQ may show distinctive effects in viral pneumonia patients, such as elevated galectin-3-binding protein and glutathione peroxidase 3 levels. Conclusion: This study provides a precise investigation of the efficacy of a multicomponent drug against viral pneumonia and offers a promising alternative for personalized management of viral pneumonia.